Public Deliberation about Gene Editing in the Wild - Gusmano, Michael K. (The Hastings Center report, 2021)
Genetic editing technologies have long been used to modify domesticated nonhuman animals and plants. Recently, attention and funding have also been directed toward projects for modifying nonhuman organisms in the shared environment—that is, in the "wild." Interest in gene editing nonhuman organisms for wild release is motivated by a variety of goals, and such releases hold the possibility of significant, potentially transformative benefit. The technologies also pose risks and are often surrounded by a high uncertainty. Given the stakes, scientists and advisory bodies have called for public engagement in the science, ethics, and governance of gene editing research in nonhuman organisms. Most calls for public engagement lack details about how to design a broad public deliberation, including questions about participation, how to structure the conversations, how to report on the content, and how to link the deliberations to policy. We summarize the key design elements that can improve broad public deliberations about gene editing in the wild.